Discovery, observations, and modelling of a new eclipsing polar: MASTER OT J061451.70–272535.5. Issue 3 (16th January 2019) - Breytenbach, H; Buckley, D A H; Hakala, P; Thorstensen, J R; Kniazev, A Y; Motsoaledi, M; Woudt, P A; Potter, S B; Lipunov, V; Gorbovskoy, E; Balanutsa, P; Tyurina, N
ABSTRACT: We report the discovery of a new eclipsing polar, MASTER OT J061451.70–272535.5, detected as an optical transient by MASTER auto-detection software at the recently commissioned MASTER-SAAO telescope. Time resolved (10–20 s) photometry with the SAAO 1.9-m and 1.0-m telescopes, utilizing the SHOC EM-CCD cameras, revealed that the source eclipses, with a period of 2.08 h (7482.9$± 3.5\, $ s). The eclipse light curve has a peculiar morphology, comprising an initial dip, where the source brightness drops to 50 per cent of the pre-eclipse level before gradually increasing again in brightness. A second rapid ingress follows, where the brightness drops by 60–80 per cent, followed by a more gradual decrease to zero flux. We interpret the eclipse profile as the result of an initial obscuration of the accretion hot-spot on the magnetic white dwarf by the accretion stream, followed by an eclipse of both the hotspot and partially illuminated stream by the red dwarf donor star. This is similar to what has been observed in other eclipsing polars such as HU Aqr, but here the stream absorption is more pronounced. The object was subsequently observed with South African Large Telescope (SALT) using the Robert Stobie Spectrograph (RSS). This revealed a spectrum with all of the Balmer lines in emission, a strong He ii 4686 Å line with a peak flux greater than that of H β, as well as weaker He i lines. The spectral features, along with the structure of the light curve, suggest MASTER OT J061451.70–272535.5 is a new magnetic cataclysmic variable, most likely of the synchronized Polar subclass.